The effects of different dosage applications of Bacillus sp. NP5 para-probiotic on the growth performance and resistance of Nile tilapia against Streptococcus agalactiae infection - Widanarni; Sukenda; Annisa Astri Anggraeni; Rr. Bellya Anasti Maharani; Aldy Mulyadin; Munti Yuhana (Jurnal Akuakultur Indonesia, 2022)
The aim of the study is to test the effectiveness of adding various paraprobiotic doses of Bacillus sp. NP5 through feed in improving the immune responses and resistance of tilapia juvenile (Oreochromis niloticus) to infection of Streptococcus agalactiae. Bacillus sp. NP5 paraprobiotic was produced through heat-inactivation at 95°C for 1 h. This study used a completely randomized design, which consisted of four treatments with three repetitions. The test feed was enriched with 1% paraprobiotic with a density of 108, 109, and 1010 CFU ml-1. The tilapia juvenile (10.29 ± 0.22 g) were reared for 30 days and on day 31, the fish was challenge tested with S. agalactiae (107 CFU ml-1) injected by intraperitoneal route unless the negative control was injected with PBS. The results of this study showed significantly improved growth performances and immune responses (P<0.05), compared to the control group after 30 days of paraprobiotic Bacillus sp. NP5 administered. The increased of immune responses in paraprobiotic of Bacillus sp. NP5 showed a higher survival rate (P<0.05), than positive control after the challenge tested with S. agalactiae. Administration of paraprobiotic Bacillus sp. NP5 through the commercial feed able to improve the growth performances, immune responses, and resistance of nile tilapia against S. agalactiae infection with the best result at dose of 1010 CFU ml-1.